The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jvh.12887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustained virologic response on risk of type 2 diabetes among hepatitis C patients in the United States

Abstract: Data regarding the impact of hepatitis C (HCV) therapy on incidence of type 2 diabetes mellitus are limited. We used the data from the longitudinal Chronic Hepatitis Cohort Study-drawn from four large US health systems-to investigate how response to HCV treatment impacts the risk of subsequent diabetes. Among HCV patients without a history of type 2 diabetes mellitus or hepatitis B, we investigated the incidence of type 2 diabetes from 12 weeks post-HCV treatment through December 2015. Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…3 Our own recent paper showed thatamong a large US cohort of patients who received antiviral treatment for HCV-patients who achieved SVR demonstrated a substantially lower risk for development of T2D than patients with treatment failure. 3 Another question raised by Mahla is whether HCV treatment improves glucose metabolism in T2D patients. Although there are a number of reports of significant decreases in haemoglobin A1c…”
Section: I N K E D C O N T E N Tmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Our own recent paper showed thatamong a large US cohort of patients who received antiviral treatment for HCV-patients who achieved SVR demonstrated a substantially lower risk for development of T2D than patients with treatment failure. 3 Another question raised by Mahla is whether HCV treatment improves glucose metabolism in T2D patients. Although there are a number of reports of significant decreases in haemoglobin A1c…”
Section: I N K E D C O N T E N Tmentioning
confidence: 99%
“…Studies from the interferon era suggested that sustained virological response (SVR) reduces the risk of future insulin resistance and T2D, 3 while other studies found no difference between treated and untreated HCV patients. 3 Our own recent paper showed thatamong a large US cohort of patients who received antiviral treatment for HCV-patients who achieved SVR demonstrated a substantially lower risk for development of T2D than patients with treatment failure. 3 Another question raised by Mahla is whether HCV treatment improves glucose metabolism in T2D patients.…”
Section: I N K E D C O N T E N Tmentioning
confidence: 99%
See 3 more Smart Citations